Making sense of reality - Corsellis, Ann (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
There is a pressing need to provide a worthwhile academic underpinning to public service or community interpreting and its professional context. This paper considers the strategies that could benefit both pure and applied research in this area by discussing a number of majorfactors. First, the approaches used by interpreting as well as related scientific re- search in the public service field to engage with the relevant range of professional practitioners in identifying the topic, gathering adequate and reliable information, seeking ways forward, developing interdisciplinary understanding and implementing improvedpractice, are considered.Second, it is argued that there is a crucial needfor interpreting and language specialists to demonstrate and apply standards of valid research methodologies equivalent to those used in other disciplines in this context (such as medicine), in order to affirm their academic responsibility and interdisciplinary credibility. Finally, the dissemination of the results of research, not only to fellow academics in the language world but also to academics in other related disciplines as well as to the practitioners - interpreters, translators, doctors, lawyers, police officers, social workers etc., is considered. Research results must be accessible in order to improve practice and to enable the research results to be brought into the mainstream informed debate.